The rules international financial information, the opportunity cost of the shareholder and decision making - Flores Delgado, Jorge (2021)
This article discusses the International Financial Reporting Standards and their role in the generation of financial information. One of the main indicators is the debt-toequity ratio, and the shareholder's cost of capital. The shareholder's cost of capital is a fundamental variable in financial decision-making, and it must be included in the financial statements under the International Financial Reporting Standards.